Stepping out of the shadows: the role of pivotal individuals in Qatar’s aspirations to host mega-events - Zumbrägel, Tobias; Sons, Sebastian (The hard edge of soft power, 2025)
The so-called Arab Spring fundamentally transformed the geographical region of West Asia and North Africa. Previous key players like Egypt and Syria lost power, while Iraq suffered from domestic conflicts and civil war as a consequence of the US-led invasion in 2003 and the disastrous postconflict management. These developments offered an opportunity for the Arab Gulf states, especially for smaller states which previously had been known for mediating international conflicts (e.g., Qatar, Kuwait, Oman) or sparkling and buzzling metropolises (e.g., the United Arab Emirates and its “Dubai Model”). These states increasingly used their influence and capacities to exert their vision over the broader region and beyond. By hosting mega-events, the Gulf monarchies aim to enhance their international credibility, engage in nation branding, and foster national identity and nationalism, all while obscuring deeper authoritarian forces behind Potemkin façades. This chapter focuses on key elites that played a crucial role in organizing two mega-events in Qatar: the climate summit (COP18) in 2012 and the FIFA World Cup 2022. In so doing, the chapter contributes to a deeper understanding that specific influential figures matter more than previously acknowledged in scholarly discussions.
Gesehen am 11.06.2025